Phytochemical Screening and Anti-Hyperuricemia Activity Test In Vivo of Ethanolic Extract of Shallot (Allium cepa L.) Skin - Syahrina Syahrina; Vivi Asfianti; Kasta Gurning; Iksen Iksen (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Uric acid is the final product of purine metabolism that will be excreted through urine, feces, and sweat. Excessive production of uric acid can cause hyperuricemia, known as gout. The skin of shallots (Allium cepa L.) is one of the household wastes that are very rarely used by the community. Ethanol extract of shallot skin (EESS) was tested for phytochemical screening and anti-hyperuricemia activity using potassium oxonate. Mice were divided into five groups (Allopurinol, Na-CMC, EESS 200 mg/kg BW, 300 mg/kg BW, and 400 mg/kg BW) and uric acid levels were observed at 2-hour intervals for six hours. Phytochemical screening shows that EESS has potential compounds in the treatment of gout. Tests to reduce uric acid levels showed that EESS has better potential than allopurinol at concentrations of 300 mg/kg BW and 400 mg/kg BW after six hours of induction in reducing uric acid levels.